Inclusivity and Sustainable Development: A Case for Zimbabwe Higher Education Towards the Universal Design University - Kudakwashe Manokore; Zibulo Sibanda; Ntandoyenkosi Gwebu (Scientia Publica Media, 2024)
Education for Sustainable Development (ESD) aims to transform society toward peace and sustainability by reorienting educational practices and learning experiences. The United Nations 2030 Agenda underscores the importance of quality education and ESD as vital components for driving the transformation of the global economy, as highlighted in its goals. In this framework, the Ministry of Higher and Tertiary Education, Innovation, Science and Technology Development (MHTEISTD) is actively implementing Education 5.0 in alignment with Sustainable Development Goal 4, which seeks to “ensure inclusive and equitable quality education and promote lifelong learning opportunities for all.” To explore the integration of inclusivity and sustainable development principles within the context of Universal Design in Higher Education, a longitudinal cohort study was conducted. This research employed structured interviews with lecturers and students, alongside observations and facility reviews, to gather diverse perspectives on the current state of inclusivity in Zimbabwean higher education. The findings indicated that while all participants demonstrated some understanding of the concept of inclusive education, the actual inclusion of students with special needs was found to vary between inadequate and acceptable levels since the implementation of Education 5.0. Based on these findings, the study strongly recommends the formal enactment of the 2019 Inclusive Education Policy draft. This policy is crucial for establishing a clear implementation framework and action plan, which are necessary for enhancing the inclusivity of higher education. By doing so, it ensures that all students, regardless of their individual needs, have equitable access to educational opportunities, thereby fostering a more inclusive and sustainable academic environment in Zimbabwe.